The Last Emperor - Bertolucci, Bernardo, 1941-; Chen, Joan.; Peter O'Toole; Ruocheng Ying; Victor Wong; 1987; France Italy UK; John Lone (US Live / Artisan, 1987)
A dramatic history of Pu Yi, the last of the Emperors of China, from his lofty birth and brief reign in the Forbidden City, the object of worship by half a billion people; through his abdication, his decline and dissolute lifestyle; his exploitation by the invading Japanese, and finally to his obscure existence as just another peasant worker in the People's Republic.
The story of the final Emperor of China.
Language: English Subtitle: Turkish
1987 Oscar Academy Award Best Picture
Keywords: Drama; Biography -- History -- Oscar Academy Award